Assessment of Cortical Dysfunction in Infantile Esotropia Using fMRI. Issue 3 (May 2014) - Yang, Xubo; Zhang, Junran; Lang, Lijuan; Gong, Qiyong; Liu, Longqian
Purpose: Functional magnetic resonance imaging (fMRI) is popular in the field of neuroimaging. The aim of this study was to explore the neural basis of infantile esotropia and locate the cortical region of fusion function defects using blood oxygen level—dependent fMRI (BOLD-fMRI). Methods: Subjects (5 with infantile esotropia and 8 normal) were presented with a visual stimulus (letter E). The BOLD-fMRI was used to measure the visual cortex response as the distance between the E and the eyes changing from 20 to 100 cm using a block experimental design. Data were processed offline using statistical parametric mapping and compared between the 2 groups. Results: Areas activated in the visual cortex of normal subjects were located in the bilateral frontal gyrus and left lingual visual cortex (p<0.001). The BOLD signal in the left cingulate gyrus, bilateral precuneus, and left angular gyrus was higher in the infantile esotropia group than in the controls (p<0.001). None of the visual cortical areas showed higher signal in the control individuals than in those with infantile esotropia (p<0.001). Conclusions: The bilateral frontal gyrus and left lingual visual cortex regulate normal fusion function in human eyes. In infantile esotropia, the left cingulate gyrus, bilateral precuneus, and left angular gyrus visual cortex may compensate for the fusion dysfunction. These insights may help improve the diagnosis and treatment of strabismus.